2022
DOI: 10.2147/ndt.s352151
|View full text |Cite
|
Sign up to set email alerts
|

Kinesiophobia in Elderly Polish Patients After Ischemic Stroke, Including Frailty Syndrome

Abstract: Introduction In patients after stroke, the relationship between the occurrence of kinesiophobia and the accompanying frailty syndrome, as well as the acceptance of the disease and the level of mood, has not been recognized so far. The aim of this study was to determine the prevalence of kinesiophobia in elderly Polish people after ischemic stroke, including the frailty syndrome and the associations between the prevalence of kinesiophobia and feelings of anxiety and degree of the illness acceptance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The results showed that 128 people (66.67%) had severe kinesiophobia, and the incidence of kinesiophobia in stroke patients was close to 80%. In addition, Bąk et al [ 61 ] conducted a cross-sectional study of 152 elderly patients with ischemic stroke in Poland, reporting that kinesiophobia was present in 78% of the patients. Sertel et al [ 62 ] found that the balance score and fall efficacy score of stroke patients were negatively correlated with the severity of kinesiophobia.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that 128 people (66.67%) had severe kinesiophobia, and the incidence of kinesiophobia in stroke patients was close to 80%. In addition, Bąk et al [ 61 ] conducted a cross-sectional study of 152 elderly patients with ischemic stroke in Poland, reporting that kinesiophobia was present in 78% of the patients. Sertel et al [ 62 ] found that the balance score and fall efficacy score of stroke patients were negatively correlated with the severity of kinesiophobia.…”
Section: Discussionmentioning
confidence: 99%
“…However, these approaches fall short in addressing the intricate pathophysiology involving systemic inflammatory responses and neurodegeneration. [ 4 , 5 ] As is well-established, a bidirectional interplay exists between the brain, the gastrointestinal tract, and the gut microbiota. The communication network linking the brain and the gut is termed the gut-brain axis (GBA), with interactions therein capable of influencing overall health and emotional states.…”
Section: Introductionmentioning
confidence: 99%